On the origin of the functional versatility of macrophages - Bajgar, Adam; Krejčová, Gabriela (Frontiers in Physiology, 2023)
Macrophages represent the most functionally versatile cells in the body. In addition to recognizing and destroying pathogens, macrophages remove senescent and exhausted cells, promote wound healing, and govern tissue and metabolic homeostasis. In addition, many specialized populations of tissue-resident macrophages exhibit highly specialized functions essential for the function of specific organs. Sometimes, however, macrophages cease to perform their protective function and their seemingly incomprehensible response to certain stimuli leads to pathology. In this study, we address the question of the origin of the functional versatility of macrophages. To this end, we have searched for the evolutionary origins of macrophages themselves as well as for the emergence of their characteristic properties. We hypothesize that many of the characteristic features of proinflammatory macrophages evolved in the unicellular ancestors of animals and that the functional repertoire of macrophage-like amoebocytes further expanded with the evolution of multicellularity and the increasing complexity of tissues and organ systems. We suggest that the entire repertoire of macrophage functions evolved by repurposing and diversification of basic functions that evolved in amoebocytes early in the evolution of metazoans under conditions barely comparable to tissues of advanced multicellular organisms. We believe that by applying this perspective we may find an explanation for the otherwise counterintuitive behavior of macrophages in some human pathologies.